MiR-3613-5p targets AQP4 to promote the progression of chronic atrophic gastritis to gastric cancer - Bi, Jian; Wang, Yufen; Wang, Yingde (Frontiers in Pharmacology, 2025)
Introduction: Gastric cancer (GC) exhibits high invasiveness, delayed diagnosis, and poor prognosis. Chronic atrophic gastritis (CAG), an initial stage within the Correa cascade, induces gastric mucosal inflammation and atrophy, promoting genetic and epigenetic alterations. MicroRNAs (miRNAs) dysregulation has been implicated in gastric tumorigenesis, yet their specific roles in CAG progression to GC remain unclear.Methods: Using clinical data from the GEO database, we identified miRNAs differentially expressed in gastric mucosa and serum samples from GC patients. Murine CAG models were established through administration of N-methyl-N-nitrosourea (MNU) and high-salt diet (HSD). In vitro functional assays evaluated proliferation and migration after miRNA modulation in gastric cancer cell lines. MiRNA target validation involved luciferase reporter assays.Results: MiR-3613-5p expression was significantly elevated in gastric mucosal and serum samples of GC patients, mucosal tissues of CAG patients, tumor tissues, and human gastric cancer cell lines. Murine models demonstrated increased miR-3613-5p expression in gastric mucosa following MNU and HSD-induced CAG. Functionally, miR-3613-5p overexpression promoted gastric cancer cell proliferation and migration in vitro, whereas silencing miR-3613-5p alleviated pathological gastric mucosal alterations (atrophy, hyperplasia, inflammatory infiltration) in vivo. Mechanistically, miR-3613-5p inhibited Aquaporin 4 (AQP4) expression by directly targeting its 3'UTR.Discussion: Our findings provide the first evidence that miR-3613-5p facilitates CAG progression toward GC via negative regulation of AQP4. These results highlight miR-3613-5p as a promising biomarker and therapeutic target, suggesting antagomiR-3613-5p as a potential novel strategy to prevent gastric carcinogenesis.